Exhaustive exercise alters thinking times in a Tower of London task in a time-dependent manner - Zimmer, Philipp (Frontiers in physiology, 2017)
Purpose: In contrast to other aspects of executive functions, acute exercise-induced alterations in planning are poorly investigated. While only few studies report improved planning performances after exercise, even less is known about their time course after exhaustive exercise. Methods: 119 healthy adults performed the Tower of London (ToL) task at baseline, followed by a graded exercise test (GXT). Participants were subsequently randomized into one of four groups (immediately, 30, 60, and 90 minutes after the GXT) to repeat the ToL. Main outcomes of the ToL were planning (number of tasks completed in the minimum number of moves), solutions (correct responses independent of the given number of moves) as well as thinking times (time between presentation of each problem and first action) for tasks with varying difficulty (four-, five- and six-move problems). Blood lactate levels were analyzed as a potential mediator. Results: No effect of exercise on planning could be detected. In contrast to complex problem conditions, median thinking times deteriorated significantly in the immediately after GXT tested group in less challenging problem conditions (four-move problems: p=.001, F=5.933, df=3; five-move problems: p=.005, F=4.548, df=3). Decreased lactate elimination rates were associated with impaired median thinking times across all groups (ΔMTT4-6 (p=.001, r=-.309), ΔMTT4 (p<.001, r=-.367) and ΔMTT5 (p=.001, r=-.290). Conclusion: These results suggest that planning does not improve within 90 minutes after exhaustive exercise. In line with previous research, revealing a negative impact of exhaustive exercise on memory and attention, our study extends this knowledge of exercise-induced alterations in cognitive functioning as thinking times as subcomponents of planning are negatively affected immediately after exercise. This is further associated with peripheral lactate levels.
Gesehen am 17.08.2018